A importância do componente cívico para o funcionamento efetivo de canais participativos como instrumentos de inclusão democrática: um estudo de caso dos Comitês Gestores de Bairro do Programa Nova Baixada - Maia, Juliana Guaraná Vieira (2006)
The present research aimed at verifying the performance, as instruments of democratic inclusion, of the managing committees (¿Comitês Gestores de Bairro¿), created by the Government of Rio de Janeiro in the scope of the Nova Baixada Program. Thus, at first, it was presented the concept of democracy, its presuppositions and fragilities, as well as some mechanisms introduced with the objective to extend the effectiveness of this regimen, like the channels of popular participation. It was also demonstrated the importance of the diffusion of civic values for the consolidation of the democracy, mainly in countries like Brazil, where determined cultural characteristics of the society use to act in a negative way in the democratization process. With this propose, some democratic theories, which value aspects as civism and social capital, had been presented and it was also analyzed the cultural elements of the Brazilian society that had negative implications in the performance of the channels of participation introduced in the country. Finally, it was examined the performance of the Comitês Gestores de Bairro (managing committees) of the Nova Baixada Program, trying to establish a relation between the structure of them and the cultural characteristics of our society.